Islam Nusantara in Global Challenges - M. Al Qautsar Pratama; Eka Octalia Indah Librianti; Maulida Dwi Agustiningsih (Advances in Humanities and Contemporary Studies, 2023)
Nusantara Islam has been transformed into a concept of renewal in Islam. Islamic concept: moderate, peaceful, tolerant framed by democracy and human rights, become a necessity in the life of the nation, state, and world. The characteristics of Indonesian Islam face many challenges amid increasingly complex problems in the world. This study seeks to explain the extent of the power and position of Indonesian Muslims to resolve global issues through Islam Nusantara. Moreover, Islam Nusantara and various historical dynamics and contemporary contexts are increasingly getting attention and becoming the focus of study from the international community. Thus, the Indonesian nation hopes to emerge as an Islamic leader of international repute to achieve the icon of the face of Islamic civilization so that Muslims can imitate it generally. In addition, this opportunity is considerable momentum because the Arabs are currently facing severe challenges with increasingly massive extremism and terrorism. The conclusion is that Islam Nusantara has strong bargaining power in overcoming various problems the Muslim community faces globally.